Sayaka Murata as a master of psychological fiction in Japan - Prof. DSc Khalliyeva Gulnoz Iskandarovna; Petrosyan Naira Romanovna (Zien Journals, 2023)
This article devoted to the Sayaka Murata's novel "Convenience Store Woman" which psychological image occupies a significant amount of the work, acquires relative independence and becomes extremely important for understanding the content of the work itself, in which a special artistic quality called psychologist arises.
Keywords: Psychologist; psychological novel; Japanese novel